2017
DOI: 10.12687/phleb2362-2-2017
|View full text |Cite
|
Sign up to set email alerts
|

Foam sclerotherapy of segments of the saphenous vein with adjuvant hyaluronan compression

Abstract: SummaryBackground: Thermal, mechano-chemical and chemical methods of vein closure are increasingly less effective in saphenous veins with diameters above 10 mm. Furthermore, increasing vein size is associated with unpleasant inflammatory reactions, in particular in locations close to sensitive structures like the skin. External compression media are not able to prevent these unwanted sequela in a tolerable way. As a possible solution, perivenous hyaluronan compression was evaluated combined with microfoam scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…They reported that reflux time and VCSS improved significantly. Great saphenous veins have even been reported to be effectively and safely treated with microfoam sclerotherapy without postoperative symptoms when the lumen of the vessel is reduced by perivenous injection of hyaluronan gel injection [29].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that reflux time and VCSS improved significantly. Great saphenous veins have even been reported to be effectively and safely treated with microfoam sclerotherapy without postoperative symptoms when the lumen of the vessel is reduced by perivenous injection of hyaluronan gel injection [29].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that reflux time and VCSS improved significantly. Great saphenous veins have even been reported to be effectively and safely treated with microfoam sclerotherapy without postoperative symptoms when the lumen of the vessel is reduced by perivenous injection of hyaluronan gel injection [29].…”
Section: Discussionmentioning
confidence: 99%
“…During the 12-month monitoring, there were no significant adverse or toxic instances recorded. Until now, there are no mentioned toxic, carcinogenic, or mutagenic consequences of hyaluronic acid or n-BCA with vascular or nonvascular applications [15][16][17][18].…”
Section: Yavuz Et Al Conducted the First Study In Deep Venous Insuffi...mentioning
confidence: 99%
“…However, perivenous internal compression is easy to perform after a learning period with improved results. According to Ragg et al, hyaluronan (hyaluronic acid) in superficial venous insufficiency, together with sclerotherapy, is suitable to [9,17]. N-butyl cyanoacrylate is also shown to be reliable and successful for intravascular use in patients with superficial venous reflux disease [22][23][24][25][26].…”
Section: Yavuz Et Al Conducted the First Study In Deep Venous Insuffi...mentioning
confidence: 99%